Clinical and bacteriological study of neonatal septicaemia in a tertiary care hospital - Khante, Sneha V.; Raut, Sharmila S. (International Journal of Research in Medical Sciences, 2017)
Background: Neonatal sepsis is a clinical syndrome of bacteraemia characterized by systemic signs and symptoms in the first month of life. It is the leading causes of neonatal mortality and morbidity. Early diagnosis and treatment with appropriate antibiotics is important to improve the prognosis of neonatal sepsis. Our objectives were to study the organisms causing neonatal septicaemia, associated risk factors, to correlate CRP with blood culture and to study mortality rate in neonatal septicaemia. Methods: The study of 2 years included clinically suspected cases of neonatal septicaemia admitted in NICU. 566 blood samples were collected, processed and isolates were identified. Maternal and neonatal risk factors were studied. CRP test was done by slide agglutination test. Results: Blood culture was positive in 205 (36.22%) cases. Among the culture positive cases, 128 (62.44%) were males and 77 (37.56%) females with male to female ratio of 1.66:1. Early onset sepsis was present in 137 (66.83%) and late onset sepsis in 68 (33.17%) cases. 107 (52.20%) were low birth weight babies. The most common neonatal risk factor was prematurity 75 (36.58%) and maternal risk factor was prolonged rupture of membrane 65 (31.71%). gram negative bacilli 144 (70.24%) were found to be common cause of sepsis than gram positive cocci 61 (29.76%), Klebsiella pneumoniae 54 (26.34%) being most common pathogen. Out of 566, CRP test was positive in 244 (43.10%) cases. Mortality rate was 23.41%. Conclusions: Neonatal septicaemia is a life-threatening emergency. The study of etiological profile and CRP test plays a significant role.